A new series of long wavelength red phosphors BaLaLiTe1-xO6:xMn4+ for plant cultivation LED. Issue 8 (15th April 2022) - Liu, Wen; Zhao, Dan; Zhang, Rui-Juan; Jia, Lei; Zhang, Li-Na; Shi, Lin-Ying
Abstract: Mn 4+ doped phosphors have been attracted more and more attention because their emitting spectra can be absorbed by chlorophyll or phytochrome (Pr and Pfr ) of plants. Herein, we prepared a new series of phosphors BaLaLiTe1- x O6 : x Mn 4+ (BLLT: x Mn 4+, x = 0.002–0.014) by solid state reaction method. Their structure and phase purity were verified by X-ray diffraction (XRD) analysis. Under 336 nm exciting, BLLT: x Mn 4+ can emit long wavelength red light at around 700 nm, which fits well with the Pfr spectra of plants. The Mn 4+ concentration was optimized to be x = 0.01, and when it was exceeded, concentration quenching would occur. The internal (IQE) and external quantum efficiency (EQE) of BLLT:0.01Mn 4+ were measured to be 32% and 23% by direct method. Besides, the BLLT:0.01Mn 4+ possesses good thermostability, remaining 76% of the integrated intensity at 423 K of that at 298 K. Hence, we think BLLT:0.01Mn 4+ have potentially applications for plant growth LED.